Etno-Forestri Orang Rimba di Taman Nasional Bukit Dua Belas Provinsi Jambi - Tresno Tresno; Nursyirwan Effendi; Rizaldi Rizaldi; Heri Doni; Try Surya Harapan; Mahdi Mutashim (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
The United Nations considers indigenous people local knowledge as a part of sustainable development. In fact, the local knowledge of Orang Rimba has transformed due to the pressure of industrialization. This article describe current ethnoforestry of Orang Rimba using ethnoscience and a multidisciplinary landscape assessment method. Data was collected by participatory observation, in-depth interviews, participatory social mapping, and plant collections, with informants being selected by purposive sampling. This research analysis uses an ethnoforestry approach. The ethnoforestry of Orang Rimba is local knowledge that regulates relationship between lowland forest taxonomy and the whole domain of life the Orang Rimba. Orang Rimba recognized various domains including Rimba Bungaron (primary forest) as related to both social organization and kinship (genah), customary (bebalai), and hunter-gather domain (merayau-nyulogh). Benuaron and Sialang (orchards and honey-producing trees) are classified as agroforestry domain and Bahumaon as rubber and oil palm plantations domain. The ethno-forestry of Orang Rimba has long been known as hunter-gather and swidden agliculture which is no longer the case as previous management of lowland forest has shifted the lives of Orang Rimba to rubber cultivation and oil palm plantation in Twelve Hill National Park.